Top Management Attributes, Psychological Capital, and Green Accounting Effectiveness in Public-Private Partnership Context - Chu, Chien-Chi; Ji, Yun; Lee, Hsiu-Yu; Lin, Yu-Ting (Frontiers in Psychology, 2019)
Through individual and/or collective psychological state affected by and demographic attributes, top managers shape the corporate culture and determines the overall strategic directions of an organization. Thus, top management attributes affect adoption for critical company-wide practices. This opinion paper discusses the implications of, and urges academic attention to, the role psychological capital plays in the relationship between top manager attributes on and the effectiveness of green accounting practices adoption in PPP (Public-Private Partnership (PPP)) context. Theoretical and practical implications are elaborated.